Santiago de Compostela, vers une redéfinition patrimoniale du chemin de pèlerinage - Nathalie Cerezales (Conserveries Mémorielles)
Despite fall of religious inclination in Occident, billions of pilgrims and tourists still go on the Pilgrimage of Camino de Santiago every year. The need to create an European identity, leaning on common patrimonial elements in the different nations, illustrates a policy of self-identification in which the Pilgrimage becomes one of its symbols. This identity, linked to the interests of several institutions like the Catholic Church or civil associations, helps the project born from this patrimonial definition and so create new touristic, sports, cultural or green strategies which represent alternative forms of regional development. The renewed pilgrimage gives a new meaning without excluding the Saint’s role but including itself in a ancient structure, which makes it one of the main goals to achieve.